Posterior deltoid shoulder tightness and greater contralateral lower limb muscle strength are associated with swimmers' shoulder pain - Matsuura, Y.; Fujimoto, T.; Koizumi, K.; Mise, T.; Edama, M.; Shimoyama, Y. (Journal of Science and Medicine in Sport, 2023)
Objectives To identify factors associated with shoulder pain in swimmers based on elastic muscle modulus, joint range of motion, and isometric muscle strength.